A Social-Democracia Alemã e o reformismo: um estudo a partir da passagem da centralidade do trabalho para a centralidade da política - Alves, Havana Maria Ribeiro (2015)
This dissertation makes a theoretical reflection about the reformist trend that fits within the Second Communist International. To this end, it reaffirms the centrality of work in Karl Marx and analyzes the passage of the centrality of work for the centrality of politics, a spin inaugurated by "reformist socialism", which the German social democracy is the best-known expression. Recalling also the negative role of politics based on Marx's early works, and in this direction, analyzes the process of formation and consolidation of the social democratic alternative, understanding the dynamics of the political movement that leads the implementation of the Second International as well, investigating the causal links that indicate the essence of capitalism transforms this historical period - namely the tendency towards concentration and centralization of capital and its entry into the stage of monopoly. Addresses also the inclusion of the reformist trend in the labor movement during the Second International, for that examines the vulgarization that Marxism suffered, within that movement, the main social democratic theory: Karl Kautsky and Eduard Bernstein. Thus, making a historical-critical rescue of the concept of "State of Social Welfare" in its core categories reaches its founding soil: the extraction of relative surplus value. In this sense, it analyzes a privileged segment within the working class, the labor aristocracy. Finally, points to the ineffectiveness of the social democratic alternative in the direction of socialism.